PEMS-on board and E3 Modeling: A Comparison between Real-World Measurement and Emissions Estimates from Construction Equipment - Apif M. Hajji M. Hajji; Aisyah Larasati; Michael P. Lewis; Huang Yue (Institute of Research and Community Outreach - Petra Christian University, 2019)
Vehicles in construction industry are typically powered by diesel engines and are considered to be an off-road source of air pollution. Air pollutant emissions include nitrogen oxides (NOx), particulate matter (PM), hydrocarbons (HC), and carbon monoxide (CO). Any engine that combusts a nonrenewable carbonaceous fuel will have net emissions of carbon dioxide (CO2). Economic-Energy-Environmental (E3) model, a statistical-modeled tool, is developed by combining a multiple linear regression (MLR) approach for modeling equipment productivity with the emissions calculation algorithm from Environment Protection Agency (EPA)’s NONROAD model. This paper compares emissions data between the field data to E3 model outputs, and determines the similarity of the two sources of fuel use data. It is expected the two data are not narrowly similar since the field data are for individual vehicles, while E3 results are based on NONROAD model, which was intended to estimate average fuel use for a fleet of Heavy-Duty Diesel (HDD) equipment.